A 3D approach to reconstitution of the adobe citadel of Bam after earthquake: a complementary interpretation of architectural heritage knowledge, aerial photogrammetry, and heterogeneous data. Issue 4 (19th May 2019) - Matini, Mohammad Reza; Andaroodi, Elham; Ono, Kinji
ABSTRACT: Post-disaster recovery of heritage sites is a challenge, and a three-dimensional (3D) approach is a key to the site's revival. This research has focused on 3D Computer Graphics (CG) reconstitution of the adobe Citadel of the city of Bam (part of World Heritage Sites) after the 2003 earthquake. The conventional 3D modeling methods have failed to reconstruct the Citadel due to few precise pre-earthquake surveys, complicated forms of adobe buildings and extensive site destruction. The research has proposed an innovative approach to enhance 3D cartography of Aerial Photogrammetry using heterogeneous data, such as photos before or after the earthquake, architectural drawings, videos, descriptive texts, etc. The highlight of the 3D reconstitution is to interpret historic adobe constructions and to understand the structure of vaults and loadbearing walls, the proportions, and geometry of space or the connection of interior and exterior facades. The Citadel is reconstituted by a wireframe CAD-based (Computer Aided Design) 3D drawing, and consequently by non-uniform rational basis spline (NURBS) surface modeling and is visualized by Virtual Reality (VR) or Augmented Reality (AR) applications. The results are distributed in a RDF-based (Resource Description Framework) website: Bam3DCG (https://www.bam3DCG.com ).